Species diversity and abundance of dinoflagellate resting cysts seven months after a bloom of Alexandrium catenella in two contrasting coastal systems of the Chilean Inland Sea. Issue 3 (3rd July 2018) - Díaz, Patricio A.; Molinet, Carlos; Seguel, Miriam; Díaz, Manuel; Labra, Gissela; Figueroa, Rosa I.
ABSTRACT: In Chile, 90% of the fish farms and major natural shellfish beds are located in the region surrounding the Inland Sea, where over the last few decades harmful phytoplankton blooms have often been observed. The onset and recurrence of bloom events are often related to the resuspension and germination of resting cysts that have accumulated in the sediments. The degree of cyst settling, accumulation and germination is highly variable between areas and depends on physical and environmental factors. To learn how differences in oceanographic exposure, amount of river runoff and bathymetry affect dinoflagellate cyst deposition, we examined the diversity and abundance of dinoflagellate resting cysts from two hydrographically contrasting coastal areas (oceanic Guaitecas Archipelago and estuarine Pitipalena Fjord) of the Chilean Inland Sea in September 2006, seven months after a bloom of Alexandrium catenella, a producer of paralytic shellfish toxin. Cyst species diversity consisted of 18 taxa, including A. catenella and the noxious species Protoceratium reticulatum, both of which have caused blooms in the study area. Our results revealed significant differences between the two study sites in terms of the abundance and diversity of resting cysts, suggesting that in the specific case of A. catenella, only Guaitecas stations have potential for cyst accumulation and successful growth of cells. However, there was no evidence of long-term resting cyst beds of A. catenella at either study site.